2006
DOI: 10.1021/bi060294m
|View full text |Cite
|
Sign up to set email alerts
|

PAR-1-Stimulated Factor IXa Binding to a Small Platelet Subpopulation Requires a Pronounced and Sustained Increase of Cytoplasmic Calcium

Abstract: We previously reported that only a subpopulation of PAR-1-stimulated platelets binds coagulation factor IXa, since confirmed by other laboratories. Since calcium changes have been implicated in exposure of procoagulant aminophospholipids, we have now examined calcium fluxes in this subpopulation by measuring fluorescence changes in Fura Red/AM-loaded platelets following PAR-1 stimulation. While fluorescence changes in all platelets indicated calcium release from internal stores and influx of external calcium, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 64 publications
3
16
1
Order By: Relevance
“…This phenomenon is universal for all strong platelet agonists. Importantly, in contrast to previous experience, 10,11 this new pathway seems not to require sustained high calcium levels: even after 40 minutes, when calcium in all platelets has reverted to the basal state, we still see formation of the PS+/Ca-platelets.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This phenomenon is universal for all strong platelet agonists. Importantly, in contrast to previous experience, 10,11 this new pathway seems not to require sustained high calcium levels: even after 40 minutes, when calcium in all platelets has reverted to the basal state, we still see formation of the PS+/Ca-platelets.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to previous reports, 2,10,11,17 not all of the PS-positive platelets sustained a high level of intracellular calcium after an initial increase. After several minutes from the beginning of activation, we could observe formation of 3 different subpopulations: (1) PS-negative platelets with low intracellular calcium level (PS-/Ca-), (2) PS-positive platelets with sustained high calcium level (PS+/Ca+) similar to those described previously, 2,10,11,17 and (3) a new subpopulation of platelets that had high PS together with unexpectedly low calcium (PS+/Ca-).…”
Section: Statisticssupporting
confidence: 71%
See 1 more Smart Citation
“…One of them has high phosphatidylserine (PS) expression on their surfaces, thereby it is highly procoagulant [3,4]. Procoagulant platelets have high level of intracellular calcium [5], which is mobilized by activation of the 1,4,5-trisphosphate (IP 3 ) signaling pathway. IP 3 formation induced by thrombin is in turn mediated by phospholipase Cβ which can be activated by Gαq proteins associated, in particular, with protease-activated receptors [6] (PAR 1 and PAR 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a previous report demonstrated that factor IXa binding to platelet and generation of activated factor Xa was prevented by the putative Ca 2+ channel-blocker of lanthanum chloride. 47 Unlike in vivo animal experiments 33,48 or atherothrombosis in humans, 2,3,6 our experiments did not include tissue factor originating from the vascular wall or ruptured atheroma. Thus, tissue factor, if it played a role in the generation of fibrin in our experiments, is limited to a blood-borne one.…”
Section: Discussionmentioning
confidence: 96%